Baseline and Dynamic Expression of Activating NK Cell Receptors in the Control of Chronic Viral Infections: The Paradigm of HIV-1 and HCV - Marras, Francesco; Bozzano, Federica; Ascierto, Maria Libera; De Maria, Andrea (Frontiers in Immunology, 2014)
Natural killer (NK) cell function is regulated by a balance between the triggering of activating and inhibitory receptors expressed on their surface. A relevant effort has been focused so far on the study of KIR carriage/expression setting the basis for NK cell education and self-tolerance. Focus on the evolution and regulation of activating NK receptors has lagged behind so far. Our understanding of activating receptor expression and regulation has recently improved by evidences derived from in vitro and in vivo studies. Virus infection – either acute or chronic – determines preferential expansion of NK cells with specific phenotype, activating receptors, and with recall-like functional activity. Studies on patients with viral infection (HIV and HCV) and specific diverging clinical courses confirm that inter-individual differences may exist in baseline expression of natural cytotoxicity receptors (NKp46 and NKp30). The findings that patients with divergent clinical courses have different kinetics of activating receptor density expression upon NK cell activation in vitro provide an additional, time-dependent, functional parameter. Kinetic changes in receptor expression thus represent an additional parameter to basal receptor density expression. Different expression and inducibilities of activating receptors on NK cells contribute to the high diversity of NK cell populations and may help our understanding of the inter-individual differences in innate responses that underlie divergent disease courses.